Desentralisasi Fiskal Dalam Pengelolaan Pendapatan Asli Daerah (PAD) Melalui Kebijakan Kenaikan Nilai Jual Objek Pajak (NJOP) Di Kota Pematangsiantar Periode 2021-2023 - Anisah Khoiriyah Damanik; Februati Trimurni (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Fiscal decentralization requires local governments to increase their independence by optimizing Regional Original Revenue (PAD). In Pematangsiantar City, one such effort is the policy of increasing the Taxable Object Sales Value (NJOP) based on Mayoral Regulation Number 4 of 2021. This study employed a descriptive qualitative method through interviews with BPKPD officials, the Mayor, the Regional People's Representative Council (DPRD), and affected communities. The study was analyzed using Herbert Simon's rational model, which includes problem definition, objectives, alternatives, and implementation. The results indicate that this policy arose from the need to increase PAD due to low fiscal independence. However, the formulation process lacked public participation and was implemented directly without a gradual mechanism, triggering community resistance. The initial impact of the policy actually decreased PAD realization, but in the following year, it resulted in a nominal increase. However, the policy implementation has not fully reflected the principles of participatory and equitable rationality.